The Currency Premium and Local-Currency Denominated Debt Costs in South Africa - Grandes, Martin (OECD Development Centre Working Papers, 2003)
One of the priorities set out in the Capital Flows Initiative of the NEPAD is to increase private capital flows to Africa, whereby providing African economies with longterm affordable and sustainable resources to finance their development. In this respect, lower debt costs may be of utmost importance in boosting investment and future output growth on the continent. This paper aims at identifying the determinants of South African currency premia - such premia usually form an important element of debt cost in developing countries - in order to assess the scope of South African economic policies for narrowing the spread on local-currency denominated debt. South Africa is one among very few emerging economies able to borrow long-term domestically and abroad in its own currency, the rand, and one of the few to have developed its domestic bond market fairly well. However, the rand nominal exchange rate has proved increasingly unstable and volatile over the last years. As a result ...